Dissecting genetic effects with imprinting - Álvarez-Castro, José M. (Frontiers in Ecology and Evolution, 2014)
Models of genetic effects are mathematical representations of a genotype-to-phenotype (GP) map that, rather than accounting for a raw map assigning phenotypes to genotypes, rely on parameters with deliberate evolutionary meaning—additive and interaction effects. In this article, the conceptual particularities of genetic imprinting and their implications on models of genetic effects are analyzed. The molecular mechanisms by which imprinted loci affect the relationship between genotypes and phenotypes are known to be singular. Despite its epigenetic nature, the (parent-of-origin-dependent) way in which the alleles of imprinted genes are modified and segregate in each generation is precisely determined, and thus amenable to be represented through conventional models of genetic effects. The Natural and Orthogonal Interactions (NOIA) model framework is here extended to account for imprinting as a tool for a more thorough analysis of the evolutionary implications of this phenomenon. The resulting theory improves and generalizes previous proposals for modelling imprinting.